Giving a Voice to the Voiceless: A Comparative Study of Al Jazeera English and Al Jazeera Arabic Coverage of the Syrian Refugee Crisis - Daoud, Alia (Auckland University of Technology, 2019)
This thesis investigates the extent to which the Al Jazeera media network has followed its commitment to provide “a voice for the voiceless” in the news coverage of the Syrian refugees' arrival in Germany in 2015. It examines if the principles and values of giving a voice to the voiceless have been applied equally in the Al Jazeera English (ALJE) and Al Jazeera Arabic (ALJA) news reports by identifying similarities and differences of the English and Arabic coverage. It applies a comparative study of news sources and news frames in the stories about the refugees’ arrival in Germany. This analysis is used to discuss the relationship between media, politics and society, and the role of journalism in facilitating public discussion about the global crisis. The study argues that the elements of journalistic practices - journalistic form, sources of news and story-telling frame - determine media’s capacity to tackle the crisis. Using a mixed method approach of quantitative content analysis and qualitative framing analysis of news text, photos, and videos, the study identifies main patterns of Al Jazeera’s English and Arabic coverage of the Syrian refugees’ arrival in Germany. The study is based on analysis of 70 news stories published by AJE and AJA online platforms from August 24 until September 31, 2015. The findings of this study reveal that Al Jazeera’s English approach to the crisis followed more strongly the libertarian model of the role of the media in society. The analysis shows Al Jazeera English provided more space for giving voices to the voiceless. The findings indicate both channels depended on official channels as main sources of information, but Al Jazeera English had more female sources of information and more interviews with refugees.
Keywords: Al Jazeera; Al Jazeera English and Arabic; Syrian refugee; global crisis; Arab media